2021
DOI: 10.1111/bjd.20090
|View full text |Cite
|
Sign up to set email alerts
|

Signalling of multiple interleukin (IL)‐17 family cytokines via IL‐17 receptor A drives psoriasis‐related inflammatory pathways

Abstract: The gene array dataset described in this publication has been deposited in NCBI's Gene Expression Omnibus and is accessible through GEO Series accession number GSE158448 (https://www.ncb i.nlm.nih.gov/geo/query/acc.cgi?acc= GSE158448).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…cytometry was impossible due to the pre-stimulation with PMA/ionomycin. The current hypothesis is further supported by Tollenaere et al, who observed the existence of few Th17 cells in human psoriatic skin lesions which produced high levels of IL-17 cytokines (22).…”
Section: Discussionsupporting
confidence: 73%
“…cytometry was impossible due to the pre-stimulation with PMA/ionomycin. The current hypothesis is further supported by Tollenaere et al, who observed the existence of few Th17 cells in human psoriatic skin lesions which produced high levels of IL-17 cytokines (22).…”
Section: Discussionsupporting
confidence: 73%
“…One of the key cytokines in psoriasis is IL‐17A, as evidenced by the high efficacy of monoclonal antibodies targeting IL‐17A or its receptor IL‐17RA for the treatment of patients with psoriasis 4 . IL‐17A signals through a receptor complex that includes IL‐17RA and IL‐17RC 5 . While IL‐17RA is expressed on multiple cell types, IL‐17RC is expressed mainly on epithelial cells 6 .…”
mentioning
confidence: 99%
“…4 IL-17A signals through a receptor complex that includes IL-17RA and IL-17RC. 5 While IL-17RA is expressed on multiple cell types, IL-17RC is expressed mainly on epithelial cells. 6 In the skin, the main target cells for IL-17A are the keratinocytes, in which IL-17A signalling leads to activation of innate immune responses with the induction of antimicrobial peptides, cytokines and chemoattractants through the activation of the nuclear factor kappa B (NF-jB), p38-MAPK, C/EBP-b and other pathways.…”
mentioning
confidence: 99%
“…Interleukin-17 is a pro-inflammatory cytokine produced by the T helper 17 (Th17) cells and plays an important role in the development and progression of inflammatory and autoimmune diseases [ 38 ]. Mechanisms underlying the complex pathogenesis of psoriasis have not been fully understood, but there is increasing evidence that the IL-17/IL-23 axis plays a crucial role in the inflammatory response in psoriasis [ 39 , 40 ]. The vitamin D 3 analogue calcipotriol used in treating psoriasis inhibited IL-23/IL-17 axis and neutrophil infiltration in psoriatic skin through the vitamin D receptor (VDR) in keratinocytes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%